Determinants of Whistleblowing Intentions: The Role of Education in Building Personal Integrity - Annisaa, Zakiatul; Nurlaeli, Suci (Asia Pacific Fraud Journal, 2022)
This study aims to find outwhetherthe independent variablesconsisting of relativism ethical orientation, moral intensity, organizational commitment, professional identity, anticipatory socialization, and locus of controlhavean effecton employee’s whistleblowing intention. In this research, integrity is peroxided on anticipatory socialization. The data used in this study was obtained from questionnaires distributed to 204 respondents of which 31% of them pursued higher education at the same institution. This research used quantitative methods with data quality tests and classical assumption tests. Theresults show that relativism ethics orientation, professional identity, and anticipatory socialization have a positive effect on whistleblowing intentions. Meanwhile, moral intensity and organizational commitment have no effect on whistleblowing intentions. Locus of Control has a negative effect on whistleblowing intentions. The results of this study are expected to contribute to providing a perspective on the importance of internalizing integrity in education and providing input to government agencies in supporting the enforcement of whistleblowing policies and disclosure of fraud effectively by understanding the factors that contribute positively to employee intentions to whistleblowing.